TEORI BIG BANG PERSPEKTIF AL-QUR'AN DAN SAINS MODERN - Novia Rahmadani; Farkhan Abdillah Latief; Nur Suci; Inas Fahiroh (JURNAL EKSPERIMENTAL : Media Ilmiah Pendidikan, 2026)
This study aims to analyze the interpretations of classical and contemporary Qur'anic exegetes concerning verses related to the origin of the universe, identify the points of convergence and divergence between these interpretations and the Big Bang theory, and explain the implications of the dialogue between revelation and science. This research employed a qualitative approach using a library research method. The data were collected from the Qur'an, classical and contemporary tafsir literature, books, and scholarly articles discussing modern cosmology. Data were analyzed using content analysis by comparing the interpretations of Qur'anic commentators with the concepts of the Big Bang theory. The findings indicate that Qur'an Chapters 21:30, 41:11, and 51:47 demonstrate conceptual correspondence with the Big Bang theory, particularly regarding the primordial unity of the universe, cosmic separation, the primordial gaseous phase, and the continuous expansion of the universe. Nevertheless, this relationship should be understood as complementary rather than literal, since the Qur'an serves as divine guidance while the Big Bang theory represents an empirical scientific explanation. This study highlights the importance of integrating revelation and scientific knowledge in advancing contemporary Islamic scholarship.